Perfil epidemiológico da mortalidade masculina do município de Cuiabá-MT, 2002-2012 - Fraga, Jeane Cristina Anschau Xavier de Oliveira (2016)
Objective: To characterize the profile of male mortality in the city of Cuiabá, Mato Grosso (MT) in the period of 2002-2012. Method: This is an epidemiological and ecological study, developed in three stages that include: characterization of 6050 records of men deaths aged between 20 and 59 years old, resident and domiciled in Cuiabá-MT, in the period 2002-2012; description of the main causes of male mortality in the city of Cuiabá-MT, in the period of 2002-2012 and the years of potential life lost due to these deaths; and trend analysis of male mortality in Cuiabá-MT, in the same period. The descriptive analysis was performed using absolute and relative frequency of data, and the calculation of standardized mortality rates. For the analysis of temporal series, the linear regression model with correction Prais-Winsten was used. Results: the profile of male mortality in the city of Cuiaba-MT showed that single men, dark skin, aged between 20 and 49 years and with low school level, die due to External Problems, Diseases of the Circulatory System and Malignancies Neoplasms. Among these three main causes, there are the deaths due to violent causes (homicides and car accidents) and chronic and degenerative diseases (Ischemic Heart Disease and Malignancies Neoplasms in the respiratory and digestive tract), and also premature mortality by External Causes. In Cuiabá- MT, the male mortality showed a modest downward trend for the General Mortality rates, Infectious and Parasitic Diseases and External Causes and growth for mortality rates by Malignancies Neoplasms. Conclusion: The results contained in this research demonstrate the worrying health deficit scenario experienced by the male population of Cuiabá-MT. Short and long term strategic actions should be taken to change this negative panorama. For this, educational, integration and awareness activities of the male population in the prevention and care spaces with their own health should be promoted in partnership with policy makers, of health and society in general.